STANDARISASI RESEP KUE INTI DI BIRUGO KECAMATAN AUR BIRUGO TIGO BALEH KOTA BUKITTINGGI - Amelia, Dessi; Baidar, Baidar; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2014)
This study the background due to the absence of standardization Kue Intirecipe. This looks in the results of observations material preparation techniquesand how to making, resulting in kue inti form of his round is less than perfect, softand oily texture, flavor less sweet and there is sticky when fried. the purpose ofthis research to found standard recipe, and the quality of the kue inti. The researchis a qualitative, with direct interviews with mothers who can be make the kue inti.Data collection techniques are interviews, observation, and documentation.Analysis using three flows of activities: reduction, presentation, and drawconclusions. This study conducted at one of the houses Birugo Bukittinggi inApril to May 2014. Based on the test results organopleptik a standard kue intirecipe that has been converted to four repetitions is found the quality in view ofthe round shape with a diameter of four cm, golden yellow color, savory of skinflavor, the sweet flavor of the contents, aromatic, and chewy textured.